Final Year Project Management System (FMS) / Aimuni Nadhrah Yazit and Ros Syamsul Hamid - Yazit, Aimuni Nadhrah; Syamsul Hamid, Ros (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Final Year Project (FYP) is a subject that undergraduate students able to propose any project or research. This project name is Final Year Project Management System (FMS). The purpose of this project is to replace the current manual system for managing FYP affairs. This project is going to develop by using web application that can be use by Faculty of Computer and Mathematical Sciences (FSKM) lecturers and students. The manual process for requesting supervisor, adding lecturers, adding examiners and others are messy and time consuming with lack of efficiency. Therefore, by developing FYP management system can make FYP affairs easy. This project target are FSKM’s students and lecturers. For this project, lecturers and students can access this system using their laptop or computer anytime and any browser, as long as they have internet. In this FMS, it has three big users which are admin, students, and lecturer. For each user, there will be a different interface and function. In this management system, admin will add lecturer’s information, student will request supervisor, lecturers will accept or reject request and other basic functions. FYP management system will provide all basic information about FSKM’s lecturers so that the students can use it for requesting a supervisor. PhpMyAdmin will be used as a platform for storing FMS data. FMS used functionality and usability testing to evaluate the system performance. The results show from both testing is good result according to the pass functions and high mean score.